2010
DOI: 10.3390/ijerph7062501
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Environmental Distribution of Lead in Some Municipalities of South-Eastern Nigeria

Abstract: Lead (Pb) levels were measured in roadside surface soils, dust particles and rain water samples from the urban cities of Enugu, Awka, Onitsha, Nnewi, Aba, Port Harcourt and Warri in Southern Nigeria in 2007 and 2008. Samples were collected during the dry season, while rain water samples were collected during the early rain (April–June), mid rain (July–August) and late rain seasons (September–October) for the two years. Soil samples were collected from traffic congested roads, dust was collected by tying a plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
4
15
0
Order By: Relevance
“…15 The possible deleterious effects of these heavy metals among occupationally exposed painters in Nigeria have also been documented. [16][17][18][19] Widespread contamination of the environment with lead (Pb) is consistent with the results of epidemiological studies that have found elevated blood Pb levels in a large proportion of Nigerian children. 16,18 In Nigeria, the recycling means of rechargeable batteries containing Co, Ni, Cr, and Cd does not conform to the standard regulatory authorities as the approach to material recovery currently taking place is labor intensive and inimical to both ecosystem and environment.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…15 The possible deleterious effects of these heavy metals among occupationally exposed painters in Nigeria have also been documented. [16][17][18][19] Widespread contamination of the environment with lead (Pb) is consistent with the results of epidemiological studies that have found elevated blood Pb levels in a large proportion of Nigerian children. 16,18 In Nigeria, the recycling means of rechargeable batteries containing Co, Ni, Cr, and Cd does not conform to the standard regulatory authorities as the approach to material recovery currently taking place is labor intensive and inimical to both ecosystem and environment.…”
Section: Introductionsupporting
confidence: 56%
“…As observed, there was no significant increase (p > 0.05) between 40% and 80% doses of the treated rats following subacute exposure. As shown in Figure 5, the rats exposed to EOMABRSL for 60 days (long-term exposure) had a significant (p < 0.05) increase in MDA content by 16 Figure 10). Figure 11 illustrates the different histopathological changes that were observed in the liver of animals that were given various doses in the study.…”
Section: Akintunde and Obohmentioning
confidence: 88%
“…Despite the negative impact environmental pollution, the Nigerian government have not paid serious attention to environmental pollution and degradation [9]. An efficient environmental remediation will be dependent on assessment of the health risk considering several age groups and the joint effort of both government, regulatory bodies and voluntary service [5].…”
Section: Introductionmentioning
confidence: 99%
“…This is an indication that the toxic elements in the electronics contaminate the urban environment. In Aba, the Pb concentrations in roadside dust from repair and control sites were higher than the Pb concentrations in roadside dust in 2007 and 2008 as reported by Nduka and Orisakwe (2010). In addition, the metal concentrations (Pb, Cd, Cr) in roadside dust from the control sites in Lagos were higher than the levels found in 2012 by Adaramodu et al in 2012.…”
Section: Extent Of Pollution As a Results Of Informal E-waste Recyclingmentioning
confidence: 59%